Creation of the image of ibn sina in the east and its peculiarities - Jumanovich, Abdukhamid Tangirov (Linguistics and Culture Review, 2021)
In fiction, the creation of historical reality and the character of a historical figure is a complex process in which artists create unique styles and genres for each event in the creation of a work of art. This can only be seen in the variety of colors used to create the image of the great oriental scholar Ibn Sina.